Business Integrative Sustainable in the BUMDesa Towards a Superior, Independent and Sustainable Village - Zuhri, Ach; Wulandari, Nurlaily; Sanjaya, Sani; Suprapti, Ike Triyuli (IMPOWERMENT SOCIETY, 2025)
This community service program aims to implement the Business Integrative Sustainable (BIS) concept at BUMDesa Mutiara Saghara in Bunder Village, Pamekasan. This village has great potential in the field of salt production, but less than optimal management has resulted in low contribution to Village Original Income (PAD) and community welfare. The method used in this service is a participatory and mentoring approach, starting from socialization, training, mentoring and evaluation. The results of the activities show development, especially in terms of managing thought patterns and beliefs. The participation of BUMDesa administrators has begun to run according to their duties and functions, they earn income from the results of their work. Community support is starting to be seen and continues to increase, starting from PKK women who help with sales so that turnover continues to increase. Apart from that, salt farmers are also enthusiastic about farming because their agricultural products are purchased by BUMDesa at prices higher than market prices. Salt edutourism is experiencing consistent development with a commitment to open every Saturday and Sunday. This program can be said to have succeeded in opening up new jobs and increasing the independence of the village economy through optimizing local potential.